The procyclicality of banking: Evidence from the euro area - Harry Huizinga; Luc Laeven (European Central Bank (ECB), 2019)
Loan loss provisions in the euro area are negatively related to GDP growth, i.e., they are procyclical. Loan loss provisions tend to be more procyclical at larger and better capitalized banks. The procyclicality of loan loss provisions can explain about two-thirds of the variation of bank capitalization over the business cycle. We estimate that provisioning procyclicality in the euro area is about twice as large as in other advanced economies. This difference reflects a larger procyclicality of provisioning in euro area countries already prior to euro adoption, and the divergent growth experiences of euro area countries following the global financial crisis.
Keywords: G20; 330; Banks; financial regulation; accounting; bank capital; loan loss provisioning; financial stability